New therapeutic directions in type II diabetes and its complications: mitochondrial dynamics - Wang, Shengnan; Zhao, Haiyang; Lin, Suxian; Lv, Yang; Lin, Yue; Liu, Yinai; Peng, Renyi; Jin, Huanzhi (Frontiers in Endocrinology, 2023)
As important organelles of energetic and metabolism, changes in the dynamic state of mitochondria affect the homeostasis of cellular metabolism. Mitochondrial dynamics include mitochondrial fusion and mitochondrial fission. The former is coordinated by mitofusin-1 (Mfn1), mitofusin-2 (Mfn2), and optic atrophy 1 (Opa1), and the latter is mediated by dynamin related protein 1 (Drp1), mitochondrial fission 1 (Fis1) and mitochondrial fission factor (MFF). Mitochondrial fusion and fission are generally in dynamic balance and this balance is important to preserve the proper mitochondrial morphology, function and distribution. Diabetic conditions lead to disturbances in mitochondrial dynamics, which in return causes a series of abnormalities in metabolism, including decreased bioenergy production, excessive production of reactive oxygen species (ROS), defective mitophagy and apoptosis, which are ultimately closely linked to multiple chronic complications of diabetes.Multiple researches have shown that the incidence of diabetic complications is connected with increased mitochondrial fission, for example, there is an excessive mitochondrial fission and impaired mitochondrial fusion in diabetic cardiomyocytes, and that the development of cardiac dysfunction induced by diabetes can be attenuated by inhibiting mitochondrial fission. Therefore, targeting the restoration of mitochondrial dynamics would be a promising therapeutic target within type II diabetes (T2D) and its complications. The molecular approaches to mitochondrial dynamics, their impairment in the context of T2D and its complications, and pharmacological approaches targeting mitochondrial dynamics are discussed in this review and promise benefits for the therapy of T2D and its comorbidities.